Self Regulated Learning untuk Meningkatkan Kemampuan Akademik Anak Beresiko - Ramadhanti, Ashya Firdausy; Sartinah, Endang Pudjiastuti (GRAB KIDS: Journal of Special Education Need, 2024)
This study aims to analyze the self regulated learning model applied to children with risk. This model has an advantage because it emphasizes a sense of responsibility and self autonomy, beside that self-regulation is compilation from academic skill and aoutonomy self. This research used review systematic method with summarizing prosedures, review and analyze research data from previous related research. The step of this review is: formulate reaearch problem, explain many things about Self Regulation Learning and characteristics of children with risk. Previous related research also reviewed to formulating the right strategy for applied Self Regulated Learning at children with risk studies. Value of that study is Self Regulated Learning is effective to improve and upgrade academic skill, certainly must be done with the right step and support system.